(untitled) (Experimental biology, 2025)
Langya henipavirus (LayV) is a novel zoonotic pathogen of the Henipavirus genus of the Paramyxoviridae family, phylogenetically related to the virulent Nipah and Hendra viruses. First identified in the eastern part of China in 2018, the pathogen captured the attention of scientific researchers because of the genomic structure, postulated animal host and its possible impact on human health. This review focuses on the virus pathogenesis of LayV, especially its genomic model, the way it infects the cells and evades immune system. The purpose of the review is to summarize the current knowledge of LayV at the molecular and virological level, with the focus put on the functioning of the genome, the method of penetration into the host cell, and the possibility to influence the immune system. Additional emphasis is placed upon comparative genomic study, the use of glycoproteins to provide attachment and fusion activity, and suggested immune evasion strategies with comparison to other species of Henipavirus. Key observations denote that LayV has a pattern of replication similar to other this type of henipaviruses, with a 6-gene RNA genome and potentially suppresses host innate immune responses. However, there are still significant uncertainty sheds, in particular with efforts to define host receptors and transmission forms. This review contributes to the field of emergent viral pathogenesis since it defines the viral pathogens biological dynamics of the LayV, thus setting the basis of future surveillance work, antiviral responses, and preparedness plans based on One Health.